AB90. Contralateral upper tract urothelial carcinoma after nephroureterectomy: the predictive role of methylation status - Zhang, Lei (Transl Androl Urol, 2014)
BACKGROUND: Aberrant methylation of cytosine-guanine dinucleotide (CpG) islands is one of the most common epigenetic modifications involved in the development of urothelial carcinoma. However, it is unknown that the predictive role of methylation to contralateral new upper tract urothelial carcinoma (UTUC) after radical nephroureterectomy (RNU). OBJECTIVE: To evaluate the role of methylation of ten genes in predicting contralateral UTUC recurrence after RNU. DESIGN, SETTING, AND PARTICIPANTS: In a retrospective design, methylation of ten genes was analyzed on tumor specimens belonging to 664 consecutive patients treated by RNU. Median follow-up was 48 mo (range, 3-144 mo). OUTCOME MEASUREMENTS STATISTICAL ANALYSIS: Gene methylation was accessed by methylation-sensitive polymerase chain reaction, and we calculated the methylation index (MI), a reflection of the extent of methylation in the ten genes. The log-rank test and Cox regression were used to identify the predictor of contralateral UTUC recurrence after RNU. RESULTS AND LIMITATIONS: Thirty (4.5%) patients developed a subsequent contralateral UTUC after a median follow-up time of 27.5 (range, 2-139) months. Promoter methylation was present in 88.9% of UTUC. Fewer methylation and lower MI were seen in the tumors with contralateral UTUC recurrence than the tumors without contralateral recurrence. Methylation for several genes was correlated with age, gender, architecture, tumor size, multifocal disease, stage, and grade. High MI was significantly correlated with poor prognostic parameters (advanced grade, increased stage, positive lymph nodes and sessile architecture) and poor cancer-specific survival. Multivariate analysis indicated that unmethylated RASSF1A, lack of bladder recurrence prior to contralateral UTUC, history of renal transplantation, and preoperative renal insufficiency are independent risk factors for contralateral UTUC recurrence after RNU. The major limitation of this study is related to its retrospective design. CONCLUSIONS: Methylation is frequent in the UTUC generally, and relative infrequent in the tumors with contralateral UTUC recurrence. Methylation is a new promising predictor of contralateral UTUC recurrence after RNU.